Do instrumental activities of daily living predict Dementia at 1- and 2-year follow-up?: findings from the development of screening guidelines and diagnostic criteria for predementia Alzheimer's disease study - Sikkes, Sietske; Visser, Pieter Jelle; Knol, Dirk L.; de Lange-de Klerk, Elly S. M.; Tsolaki, Magda; Frisoni, Giovani B.; Nobili, Flavio; Spiru, Luiza; Rigaud, Anne Sophie; Frölich, Lutz; Rikkert, Marcel Olde; Soininen, Hilkka; et al. (Journal of the American Geriatrics Society, 2011)
Objectives To investigate whether problems in instrumental activities of daily living (IADL) can add to conventionally used clinical measurements in helping to predict a diagnosis of dementia at 1- and 2-year follow-up. Design Multicenter prospective cohort study. Setting Memory clinics in Europe. Participants Individuals aged 55 and older without dementia. Measurements IADLs were measured using pooled activities from five informant-based questionnaires. Structural equation modeling (SEM) was used to investigate the relation between IADLs and dementia. Age, sex, education, depression, and cognitive measures (Mini-Mental State Examination and verbal memory) were included in the model. Results Five hundred thirty-one participants had baseline and 1-year follow-up assessments; 69 (13.0%) of these had developed dementia at 1-year follow-up. At 2-year follow-up, 481 participants were seen, of whom 100 (20.8%) had developed dementia. Participants with IADL disabilities at baseline had a higher conversion rate (24.4%) than participants without IADL disabilities (16.7%) (chi-square = 4.28, degrees of freedom = 1, P = .04). SEM showed that IADL disability could help predict dementia in addition to the measured variables at 1-year follow-up (odds ratio (OR) = 2.20, 95% confidence interval (CI) = 1.51-3.13) and 2-year follow-up (OR = 2.11, 95% CI = 1.33-3.33). Conclusion IADL disability is a useful addition to the diagnostic process in a memory clinic setting, indicating who is at higher risk of developing dementia at 1- and 2-year follow-up.